Interface bond degradation and damage characteristics of full-length grouted rock bolt in tunnels with high temperature - Yunpeng Hu; Mingming Zheng; Wenkai Feng; Jianjun Tong; Yicheng Wang; Qiling Wang; Kan Liu; Longzhen Ye (Journal of Rock Mechanics and Geotechnical Engineering, 2023)
Full-length grouted bolts play a crucial role in geotechnical engineering thanks to their excellent stability. However, few studies have been concerned with the degrading performance of grouted rock bolts caused by extensive and continuous heat conduction from surrounding rocks in high-geothermal tunnels buried more than 100 m (temperature from 28 °C to 100 °C). To investigate the damage mechanism, we examined the time-varying behaviors of grouted rock bolts in both constant and variable temperature curing environments and their damage due to the coupling effects of high temperature and humidity through mechanical and micro-feature tests, including uniaxial compression test, pull-out test, computed tomography (CT) scans, X-ray diffraction (XRD) test, thermogravimetric analysis (TGA), etc., and further analyzed the relationship between grout properties and anchorage capability. In order to facilitate a rapid assessment and control of the anchorage performance of anchors in different conditions, results of the interface bond degradation tests were correlated to environment parameters based on the damage model of interfacial bond stress proposed. Accordingly, a thermal hazard classification criterion for anchorage design in high-geothermal tunnels was suggested. Based on the reported results, although high temperature accelerated the early-stage hydration reaction of grouting materials, it affected the distribution and quantity of hydration products by inhibiting hydration degree, thus causing mechanical damage to the anchorage system. There was a significant positive correlation between the strength of the grouting material and the anchoring force. Influenced by the changes in grout properties, three failure patterns of rock bolts typically existed. Applying a hot-wet curing regime results in less reduction in anchorage force compared to the hot-dry curing conditions. The findings of this study would contribute to the design and investigations of grouted rock bolts in high-geothermal tunnels.